Morphdynamics of Beaches in the Tróia-Sines Littoral Ribbon (SW Portugal) - Gama, Cristina (2012)
In the Tróia-Sines littoral ribbon five beaches were monitored in order to evaluate morphological and textural changes. The textural analysis reveals a southward coarsening trend that reflects an increase in the wave energy. The morphodynamic data indicate that the modal stages are intermediate to reflective, and that the available beach volume increases southwards. During storm periods the volumetric changes reach 15% to 82% of the beach envelope corresponding to magnitudes of 6x10 3 to 2x10 5 m3/km of coast.